Onset and progression of postmortem histological changes in the kidneys of RccHanTM:WIST rats - de Miguel, Ricardo; Vallejo, Raquel; Kegler, Kristel; Kreutzer, Robert; Mayoral, Francisco José; Okazaki, Yoshimasa; Ortega, Paula; Polledo, Laura; Razinger, Tanja; Richard, Olivia Kristina; Sanchez, Raúl; Warfving, Nils; et al. (Frontiers in Veterinary Science, 2025)
IntroductionDeath initiates a cascade of physiological and biochemical alterations in organs and tissues, resulting in microscopic changes that challenge the histopathological evaluation. The aim of this study was to compile and illustrate the microscopic changes in the kidneys of rats subjected to delayed postmortem fixation. It also scrutinizes the influence of exsanguination, cooling methods and air circulation on the initiation and progression of these alterations.MethodsTwenty-four Wistar Han outbred rats (RccHanTM:WIST) were sacrificed and stored either at room temperature (18–22°C; half of the carcasses were exsanguinated after sacrifice) or under refrigeration (2–4°C). Necropsies were conducted at different time points postmortem (i.e., 0.5, 1, 4, 8, 12, 24, 36, 48 h for carcasses stored at room temperature, and 7 and 14 days for carcasses stored under refrigeration). Kidney sections underwent simultaneous digital evaluation by 14 pathologists until a consensus was reached on the key findings, terminology, and intensity levels.ResultsWhen stored at room temperature, the first changes were seen after 4 h, and involved distal convoluted tubules and inner stripe of the outer medulla. After 8 h, all structures except glomeruli were affected. Alterations were similar in quality and intensity after 36 h as after 48 h. Exsanguination delayed the onset of postmortem changes and slightly decreased their overall severity at any given timepoint. The nature of the changes under refrigeration was like those alterations noted in animals stored at room temperature. The intensity of postmortem changes observed after 7 and 14 days under refrigeration was similar to those recorded after 48 h at room temperature. No clear differences were observed between animals stored in a closed plastic bag and animals stored in a perforated cardboard box to allow air circulation.ConclusionThis work elucidates the onset and progression of postmortem changes in the kidneys of Wistar Han rats, offering insights to accurately differentiate them from real changes and enhance histopathological evaluation.